2003
DOI: 10.1046/j.1365-246x.2003.01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Pwave amplitudes in a 3-D earth

Abstract: SUMMARY Evidence is presented here that P wave amplitudes contain additional information on the Earth's heterogeneity and must be considered in future tomographic interpretations. We analyse the reliability and the variance of teleseismic P wave amplitudes recorded at well calibrated broadband Global Seismic Network (GSN) stations from intermediate to deep earthquakes (depth >46 km). The dataset contains 217 earthquakes with mb between 5.6 and 7.6, from 1993 January to 2000 May. Using pairs of closely located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…Since variations in velocity and attenuation both affect wave amplitudes, a joint inversion for velocity and attenuation is called for. In addition, ray theory does not model the frequency dependence of the effects of focusing, which is observed in practice (Allen et al 1999;Tibuleac et al 2003;Sigloch & Nolet 2006). Attempts to eliminate the effects of focusing in surface waves were first made by Romanowicz (1990) and Durek et al (1993), and were recently followed by successful attempts to invert for velocity and attenuation jointly (Billien et al 2000;Dalton & Ekström 2006).…”
mentioning
confidence: 99%
“…Since variations in velocity and attenuation both affect wave amplitudes, a joint inversion for velocity and attenuation is called for. In addition, ray theory does not model the frequency dependence of the effects of focusing, which is observed in practice (Allen et al 1999;Tibuleac et al 2003;Sigloch & Nolet 2006). Attempts to eliminate the effects of focusing in surface waves were first made by Romanowicz (1990) and Durek et al (1993), and were recently followed by successful attempts to invert for velocity and attenuation jointly (Billien et al 2000;Dalton & Ekström 2006).…”
mentioning
confidence: 99%
“…Tibuleac et al, 2003;Sigloch et al, 2006Sigloch et al, , 2008. Tibuleac et al, 2003;Sigloch et al, 2006Sigloch et al, , 2008.…”
Section: Amplitudesunclassified
“…The relative rms amplitude misfit between real and synthetic waveforms is defined through the equations where u i and u 0 i are assumed to be already windowed to a particular phase or a specific part of the seismogram. Tibuleac et al (2003) demonstrated that E rms for P waves contains information about the Earth's structure. The corresponding sensitivity kernels have been derived by Dahlen & Baig (2002).…”
Section: Interrelations Between Objective Functionals and Their Assmentioning
confidence: 99%